2016
DOI: 10.1111/1471-0307.12340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus plantarum on the survival of acid‐tolerant non‐O157 Shiga toxin‐producing E. coli (STEC) strains in fermented goat's milk

Abstract: The ability of goat's milk fermented with a Lactobacillus plantarum strain B411, and in combination with commercial starter culture, to inhibit acid‐adapted (AA) and non‐acid‐adapted (NAA) environmental non‐O157 STEC strains was investigated. Acid‐adapted and NAA non‐O157 STEC strains were not inhibited in the L. plantarum‐fermented goat's milk, while the goat's milk fermented with the combination of L. plantarum and starter culture inhibited AA more than NAA non‐O157 STEC strains. Environmental acid‐tolerant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…bulgaricus and Streptococcus salivarus subsp. thermophilus) that inhibited non-O157 E.coli strains (Fayemi and Buys, 2017). In another study it was shown that yogurt starters had no adverse effect on E.coli O157:H7 individually but showed an antimicrobial effect when used together (Dineen et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…bulgaricus and Streptococcus salivarus subsp. thermophilus) that inhibited non-O157 E.coli strains (Fayemi and Buys, 2017). In another study it was shown that yogurt starters had no adverse effect on E.coli O157:H7 individually but showed an antimicrobial effect when used together (Dineen et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…The reason for that is reported to be the high antimicrobial substances produced from the beginning (Ogueke, 2008). In the studies conducted on fermented milk and dairy products, the reasons for the decrease in the number of pathogenic microorganisms during fermentation and storage were reported as the number and type of lactic acid bacteria as well as the substances which are produced during acidic fermentation such as organic acid, hydrogen peroxide, bacteriocin, diacetyl, ethanol (Dineen et al, 1998;Leistner, 2000;Rogga et al, 2005;Dikici, 2008;Ogueke, 2008;Callon et al, 2016;Fayemi and Buys, 2017;Bellio et al, 2018). STEC O26 and O111 maintained their viability during storage of 20 days.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, goat milk has a qualitative resemblance to cow milk. However, goat milk offers better digestibility, higher iron and magnesium bioavailability, and conjugated linoleic acid and essential fatty acid contents, and lower risk of allergies when compared to cow milk, encouraging consumption and development of goat milk products (Fayemi and Buys ; Verruck et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for that is reported to be the high antimicrobial substances produced from the beginning (Ogueke, 2008). In the studies conducted on fermented milk and dairy products, the reasons for the decrease in the number of pathogenic microorganisms during fermentation and storage were reported as the number and type of lactic acid bacteria as well as the substances which are produced during acidic fermentation such as organic acid, hydrogen peroxide, bacteriocin, diacetyl, ethanol (Dineen et al, 1998;Leistner, 2000;Rogga et al, 2005;Dikici, 2008;Ogueke, 2008;Callon et al, 2016;Fayemi and Buys, 2017;Bellio et al, 2018). STEC O26 and O111 maintained their viability during storage of 20 days.…”
Section: Discussionmentioning
confidence: 99%